Sodium bicarbonate ingestion and repeated swim sprint performance - Siegler, J. C.; Gleadall-Siddall, D. O. (The Journal of Strength and Conditioning Research, 2010)
The purpose of the present investigation was to observe the ergogenic potential of 0.3 g/kg of sodium bicarbonate (NaHCO3) in competitive, nonelite swimmers using a repeated swim sprint design that eliminated the technical component of turning. Six male (181.2 ± 7.2 cm; 80.3 ± 11.9 kg; 50.8 ± 5.5 ml/kgmin VO2max) and 8 female (168.8 ± 5.6 cm; 75.3 ± 10.1 kg; 38.8 ± 2.6 ml/kg·min VO2max) swimmers completed 2 trial conditions (NaHCO3 [BICARB] and NaCl placebo [PLAC]) implemented in a randomized (counterbalanced), single blind manner, each separated by 1 week. Swimmers were paired according to ability and completed 8, 25-m front crawl maximal effort sprints each separated by 5 seconds. Blood acid-base status was assessed preingestion, pre, and postswim via capillary finger sticks, and total swim time was calculated as a performance measure. Total swim time was significantly decreased in the BICARB compared to PLAC condition (p = 0.04), with the BICARB condition resulting in a 2% decrease in total swim time compared to the PLAC condition (159.4 ± 25.4 vs. 163.2 ± 25.6 seconds; mean difference = 4.4 seconds; 95% confidence interval = 8.7-0.1). Blood analysis revealed significantly elevated blood buffering potential preswim (pH: BICARB = 7.48 ± 0.01, PLAC = 7.41 ± 0.01) along with a significant decrease in extracellular K+ (BICARB = 4.0 ± 0.1 mmol/L, PLAC = 4.6 ± 0.1 mmol/L). The findings suggest that 0.3 g/kg NaHCO3 ingested 2.5 hours before exercise enhances the blood buffering potential and may positively influence swim performance.